2008
DOI: 10.1002/gcc.20615
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate tumor suppressor genes inactivated by promoter methylation in melanoma

Abstract: Tumor suppressor genes (TSGs) are sometimes inactivated by transcriptional silencing through promoter hypermethylation. To identify novel methylated TSGs in melanoma, we carried out global mRNA expression profiling on a panel of 12 melanoma cell lines treated with a combination of 5-Aza-2-deoxycytidine (5AzadC) and an inhibitor of histone deacetylase, Trichostatin A. Reactivation of gene expression after drug treatment was assessed using Illumina whole-genome microarrays. After qRT-PCR confirmation, we followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 52 publications
0
54
1
Order By: Relevance
“…We also observed enrichment for miR-129 target sites in down-regulated transcripts in vitro following T24 cell transfection with miR-129 precursor. Among the downregulated miR-129 targets, we found TP53INP1, which has been shown to have a tumor suppressor function in melanoma (45), and BMPR2, which has been reported to be associated with development of colorectal cancer (46). We showed that the down-regulated targets SOX4 and GALNT1 were direct targets for miR-129 in luciferase assays.…”
Section: Discussionmentioning
confidence: 78%
“…We also observed enrichment for miR-129 target sites in down-regulated transcripts in vitro following T24 cell transfection with miR-129 precursor. Among the downregulated miR-129 targets, we found TP53INP1, which has been shown to have a tumor suppressor function in melanoma (45), and BMPR2, which has been reported to be associated with development of colorectal cancer (46). We showed that the down-regulated targets SOX4 and GALNT1 were direct targets for miR-129 in luciferase assays.…”
Section: Discussionmentioning
confidence: 78%
“…TIMP3 has been shown to inhibit tumor growth, invasion and angiogenesis, and has previously been established as a hypermethylated and downregulated gene in breast cancer (Lui et al, 2005). TP53INP1, which plays a role in both cell cycle arrest and p53-mediated apoptosis (Weng et al, 2011), has been shown to be decreased in melanoma and its reduced expression was correlated with hypermethylation of a promoter (Bonazzi et al, 2009). Notable cancer-related genes within the TNF-α-dependent apoptosis pathways that were upregulated in the Aza-treated MCF-7 cells included TNFSF10 (2.1-fold increase in both 5 and 10 μM Aza treated cells) and ICAM1 (2.3-fold increase in both 5 and 10 μM Aza treated cells).…”
Section: Aza Induced Genome-wide Demethylation In Mcf-7 Cellsmentioning
confidence: 99%
“…IL-6, a target of C/EBP␤, is a mediator of the oncogene-induced senescence program triggered by the oncogenic BRAF E600 allele in human fibroblasts (51). The gene for PPP1R3C (protein phosphatase 1 regulatory subunit 3C) is hypermethylated in several cancers and is a candidate tumor suppressor gene (52)(53)(54)(55)(56). CBLB (Cas-Br-M retroviral transforming sequence b), a member of the Cbl family of ubiquitin ligases, promotes mono-ubiquitination of proteins targeted for lysosomal degradation (57).…”
Section: Discussionmentioning
confidence: 99%